Static: Low Frequency Energy Harvesting and Power Transfer for the Internet of Things - Thangarajan, Ashok Samraj; Nguyen, Thien Duc; Liu, Mengyao; Michiels, Sam; Yang, Fan; Man, Ka Lok; Ma, Jieming; Joosen, Wouter; Hughes, Danny (Frontiers in Signal Processing, 2022)
The Internet of Things (IoT) is composed of wireless embedded devices which sense, analyse and communicate the state of the physical world. To achieve truly wireless operation, today’s IoT devices largely depend on batteries for power. However, this leads to high maintenance costs due to battery replacement, or the environmentally damaging concept of disposable devices. Energy harvesting has emerged as a promising approach to delivering long-life, environmentally friendly IoT device operation. However, with the exception of solar harvesting, it remains difficult to ensure sustainable system operation using environmental power alone. This paper tackles this problem by contributing Static, a radio frequency energy harvesting and wireless power transfer platform. Our approach comprises autonomous energy management techniques, adaptive power transfer algorithms and an open-source hardware reference platform to enable further research. We evaluate Static in laboratory conditions and show that (i.) ambient RF energy harvesting can deliver sustainable operation using common industrial sources, while (ii.) wireless power transfer provides a simple means to power motes at a range of up to 3m through a variety of media.